Movimentos sociais na saúde: Construindo a advocacia de casos e causas - Caroline Gomes de Souza (2016)
In Brazil, social movements have built their stories with agendas that seek to guarantee social rights as citizenship exercise. In the health sector, these movements organize their struggles, claims and defenses without mention advocacy in health issue. The health law is a competence for health promotion. It can be focused on cases with specific actions taken by individuals or small groups, or on actions related to public policy. In this study we have presupposition that the law is expressed in the defense case. It was proposed as a general objective to analyze the health advocacy in areas of fighting, claim and protection. It is a qualitative research with methodological approach of multiple case study in the context of case law and causes in spaces of struggle, claim and health defense: Central Popular Movements (CMP); the Popular Movement of Health (MOPS) and the National Movement of Street People (MNPR). Data were obtained from documents, observations and interviews with participants of the three social movements. The empirical material was discussed under the guidance of the Critical Discourse Analysis. The results are organized into five sections: 1) A brief history of social movements, 2) The political context of the movements, 3) Street: performance space of movements, 4) The social movements struggle and 5) Fighting, claim and health defense. The findings indicate that there are similarities and differences in the history and composition of the studied social movements. For all of them, social networks are a strategy to publicize their struggles but, in spite of its potential, do not constitute laws areas. The movements are organized according to the historical context. Often, they are subordinate to political party influence, revealing the social practice in defense of popular participation. The social movements use to appropriate institutional spaces as a way of pressure and mobilization. The streets are used, beyond traffic space, as housing and battles. It is a free expression place of the participating subjects in the movements: people who share common situations but know their rights and fight for them. The current political and economic context reflect in the actions of social movements. It was possible to identify different advocacy strategies, such as: cooperation with the government, raising awareness of the movement struggles, educational material development, partnerships with institutions, public occupation spaces and social control. In the struggles field, claims and health defense, there are influences of the biomedical model, manifested by the speech of the hegemony health concept as absence of disease. On the other hand, there are indications of a social practice that recognizes health as a universal right and, also, a need for shared and participatory management in the Unified Health System. It is concluded that the law cases and causes is being built by social movements in different spaces, enabling the consolidation of social rights in the country.